Remap-GI in Biology Learning: Enhancing Creative Thinking and Cognitive Outcomes on Biodiversity Topics - Bea Hana Siswati; Alwiana Hamidah Nugroho; Aulia Fitrotun Nurullah; Nadia Fatimah Az Zahra; Avril Ley Ann R. Llave (Al Jahiz, 2026)
Creative thinking is an essential skill that must be explicitly and systematically taught in classrooms because of its significant contribution to student learning outcomes. However, many schools still rely on conventional teaching methods, which often lead to student boredom, reduced motivation, and low engagement. Therefore, an effective learning model is needed to address this issue. This study examines the effect of the Reading Map Group Investigation (Remap-GI) learning model on cognitive learning outcomes and creative thinking skills in Biodiversity material at SMAN 1 Muncar. This study employed a quantitative quasi-experimental approach using a non-equivalent control group design. The sample consisted of 70 students (36 in the experimental group and 34 in the control group) selected through random sampling. Creative thinking data were collected using open-ended test items based on four indicators, while cognitive learning outcomes were measured using pre-test and post-test scores. Data were analyzed using Analysis of Covariance (ANCOVA), preceded by normality and homogeneity tests. The results showed that the ANCOVA test for creative thinking skills produced a significance value of 0.000 (p < 0.05), indicating that the Remap-GI model significantly improved students’ creative thinking compared to the control group. Similarly, the ANCOVA test for cognitive learning outcomes also showed a significance value of 0.000 (p < 0.05), indicating a positive effect on students’ cognitive performance. Practically, this model can be an alternative teaching strategy to reduce boredom, increase active participation, and improve conceptual understanding, especially in agro-industrial school environments where students need support in developing independent learning habits.